Wood cement board from Sesendok (Endospermum diadenum) / Mohd Arif Fikri Mohamad Adnan, Ahmad Firdaus Mat Hedzir and Ahmad Syafiq Badrul Hisham - Mohamad Adnan, Mohd Arif Fikri; Mat Hedzir, Ahmad Firdaus; Badrul Hisham, Ahmad Syafiq (2008)
Wood cement board is one of the alternative composite products to reduce the usage of raw material nowadays. So, we have chosen to make a research on cement board using Sesendok (Endospermum diadenum). The reason we selected this species is because the tree is easily available and fast growing. Plus, it is not yet widely used in wood industry. We decided to make three wood cement ratios which are 1:2.25, 1:2.5 and 1 :3.0. We also decided to use three types of additives which are Aluminium Sulfate, Sodium Silicate and Aluminium Sulfate mixed with Sodium Silicate. That is the parameters that we're going to use. The properties of the wood cement board will be determined by several type of test. The result shows the wood cement ratio uses are affected the properties of the board. By using the Malaysia standard (MS936: 1986), the board were met the requirement.